2014
DOI: 10.4103/2277-9175.124631
|View full text |Cite
|
Sign up to set email alerts
|

Prophylactic administration of aminophylline plus dexamethasone reduces post-dural puncture headache better than using either drug alone in patients undergoing lower extremity surgery

Abstract: Background:Post-dural puncture headache (PDPH) is a known complication of neuroaxial anesthesia and may be associated with significant morbidity. As invasive treatment for PDPH has known complications, pharmacologic management may be preferable. The main objective of the present study was to evaluate the effects of combining administration of intravenous aminophylline and dexamethasone on PDPH in patients who underwent lower extremity surgery in comparison with using either drug alone and also comparing them w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 18 publications
0
15
0
1
Order By: Relevance
“…They concluded that Combine administration of aminophylline 1.5 mg/kg plus dexamethasone 0.1 mg/kg significantly reduced PDPH better than using either drug alone in patients who underwent lower extremity surgery. Postoperative analgesic requirement was significantly less in groups A, D, and AD compared with group P. The results of this study did not show any significant adverse effect such as tachycardia or restlessness due to study drug administration (21) .…”
Section: In Addition Chuanjie Et Al (2018)mentioning
confidence: 50%
“…They concluded that Combine administration of aminophylline 1.5 mg/kg plus dexamethasone 0.1 mg/kg significantly reduced PDPH better than using either drug alone in patients who underwent lower extremity surgery. Postoperative analgesic requirement was significantly less in groups A, D, and AD compared with group P. The results of this study did not show any significant adverse effect such as tachycardia or restlessness due to study drug administration (21) .…”
Section: In Addition Chuanjie Et Al (2018)mentioning
confidence: 50%
“…At present, the mechanism by which aminophylline prevents PDPH remains unclear, but it may be related to the inhibition of calcium uptake by the endoplasmic reticulum of endothelial cells, stimulation of sodium and potassium pumps, increased secretion of cerebrospinal fluid, contraction of intracranial blood vessels by blocking adenosine receptors and blocking the transmission of pain perception. 20…”
Section: Discussionmentioning
confidence: 99%
“…Подаци који су коришћени у истраживању прикупљени су из медицинске историје испитаника и у интервјуу, коришћењем анкетног упитника. Интервју је обављан 24 h након буђења пацијента из анестезије (18). Анкетни упитник је специјално дизајниран за потребе ове студије и њиме су прикупљени следећи подаци: животна доб испитаника, пол, образовање, пребивалиште, позитивна историја главобоља, породична историја главобоља, тип операције, конзумација цигарета, алкохола и унос кофеина.…”
Section: болесници и методеunclassified